2020
DOI: 10.1186/s12938-020-0753-z
|View full text |Cite
|
Sign up to set email alerts
|

Data anomalies and apparent reporting errors in ‘Randomized controlled trial testing weight loss and abdominal obesity outcomes of moxibustion’

Abstract: Randomized controlled trials (RCTs) are the best method to determine causal effects for treatments if they are well done and well reported. Good evidence about proposed treatments for obesity is needed, and Hsieh et al. [1] are to be commended for putting moxibustion to the test. However, careful evaluation of the paper, similar to a prior review of another paper on moxibustion [2], reveals inconsistencies and apparent reporting errors, which raise doubts about conclusions from the study.The primary concern re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Conclusions from secondary analyses were affected, however, such as the 5-year change in body weight and waist circumference, which changed statistical significance for the olive oil group [24]. Use of statistical principles to examine the likelihood that randomization was properly implemented has flagged other studies related to nutrition and obesity, too [25][26][27][28]. In at least four cases, publications were retracted [22,26,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Conclusions from secondary analyses were affected, however, such as the 5-year change in body weight and waist circumference, which changed statistical significance for the olive oil group [24]. Use of statistical principles to examine the likelihood that randomization was properly implemented has flagged other studies related to nutrition and obesity, too [25][26][27][28]. In at least four cases, publications were retracted [22,26,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 , 20 ] In one previous clinical trial, Mestre et al found that obesity index decreased and the rate of body weight gain was slowed after the moxibustion treatment. [ 21 ] Another study conducted by Huang et al [ 22 ] showed that moxibustion was effective in reducing blood lipid indexes and the levels of Leptin, Resistin for the patients with obesity complicated with hyperlipidemia. All of these results suggest that moxibustion has beneficial effects on both body weight management and blood lipids.…”
Section: Introductionmentioning
confidence: 99%